Exploring communal harmony of Malaysia's culturally and religiously diverse society - Min, Keqin; Mai, Jianjun (2024)
This paper explores the communal harmony of Malaysia’s culturally and religiously diverse society including various ethnic groups with different religious and cultural backgrounds. It aims to investigate the role of Malaysia’s leadership in promoting such harmony and what are the right approaches to granting adequate management and sustainability. Contemporary Malaysia’s diverse community composition allows the Malaysian government to interact with Muslim and nonMuslim communities consisting of Malay, Chinese, and Indian races, for fostering social harmony in the country. This study is crucial as it discusses essential values that have contributed to the communal harmony between the adherents of various religious communities in Malaysia. Descriptive and analytical methods are used in the entire research. The focus of the discussion is on, the political setting of Malaysia, its cultural and educational diversity, inter-faith dialogue efforts in Malaysia, political endeavour in fostering social harmony, and social constructive moral values. The findings of this study conclude that communal harmony in Malaysia’s multiethnic, multireligious, multicultural, multiracial, and multilingual community, is promoted by the double-sided efforts of both Malaysia’s leaders and people by contributing to the future of the country’s development